(untitled) (Texas Journal of Philology, Culture and History, 2023)
The art of translation is a difficult and at the same time an honorable job. To translate a work of art, one must be a poet-writer, and he must also have a second talent - the ability to translate. One of the most important conditions is that the translator is not only fluent in his native language, but also very fluent in the language of the work being translated, and quickly recognizes their subtleties. The translator must be a person with a wide range of general knowledge, rich life experience, and an advanced culture. The translator must know the life and living conditions of the people he is translating from